Analysing emergent time within an isolated Universe through the application of interactions in the conditional probability approach - Bryan, Kate Louise Halse (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2020)
Time remains a frequently discussed issue in physics and philosophy. One interpretation of growing popularity is the 'timeless' view which states that our experience of time is only an illusion. The isolated Universe model, provided by the Wheeler-DeWitt equation, supports this interpretation by describing time using clocks in the conditional probability interpretation (CPI). However, the CPI customarily dismisses interaction effects as negligible creating a potential blind spot which overlooks the potential influence of interaction effects. Accounting for interactions opens up a new avenue of analysis and a potential challenge to the interpretation of time. In aid of our assessment of the impact interaction effects have on the CPI, we present rudimentary definitions of time and its associated concepts. Defined in a minimalist manner, time is argued to require a postulate of causality as a means of accounting for temporal ordering in physical theories. Several of these theories are discussed here in terms of their respective approaches to time and, despite their differences, there are indications that the accounts of time are unified in a more fundamental theory. An analytic analysis of the CPI, incorporating two different clock choices, and a qualitative analysis both confirm that interactions have a necessary role within the CPI. The consequence of removing interactions is a maximised uncertainty in any measurement of the clock and a restriction to a two-state system, as indicated by the results of the toy models and qualitative argument respectively. The philosophical implication is that we are not restricted to the timeless view since including interactions as agents of causal interventions between systems provides an account of time as a real phenomenon. This result highlights the reliance on a postulate of causality which forms a pressing problem in explaining our experience of time.
Keywords: Space and time; Quantum gravity; Quantum theory; Relativity (Physics)